Destination Image and Brand Value as Predictors of Tourist Behavior: Happiness as a Mediating Link - Deyber Jimenez-García; Ovet Espinoza Heredia; Eduar Cruz Lizana; Jose Joel Cruz-Tarrillo; Dany Yudet Millones-Liza (Administrative Sciences)
Tourism has become one of the most important industries in the business world, significantly impacting various economies. In order to have a better understanding of tourist behavior, this study aims to examine the image of the destination and the value of the brand as predictors of the behavior of tourists, assuming happiness as a mediating link. From a quantitative, non-experimental and cross-sectional methodological perspective, the information of a sample of 425 tourists was analyzed. The results support that tourist happiness predicts their intention to revisit a tourist destination (Path Coefficient 0.921). Also, tourist happiness and the intention to revisit predict the intention to recommend a tourist place. These results suggest that tourist happiness plays a fundamental role in aspects such as loyalty and the promotion of a destination, so it is important for tourism companies to promote tourist happiness as a marketing strategy that drives them to word-of-mouth recommendations and the intention to revisit a tourist destination.